Measuring Employee Performance through Emotional Intelligence with Gender Perspective - Maya Yusnita; Hamsani Hamsani; Dilla Augustine Kolina (Indonesian Management and Accounting Research, 2019)
This study was motivated by the fact that performance achievement at BKKBN (The National Population and Family Planning Board) of Bangka Belitung Islands Province in 2016-2018 was less than standard. This study investigated the effect of emotional intelligence and gender on employee performance of BKKBN of Bangka Belitung Islands Province. A quantitative descriptive study was used to collect data from 49 employees who were selected by saturated sampling technique. Data were analysed by using SPSS software. The findings show that emotional intelligence has positive and significant effect on employee performance. From gender perspective, there is no difference between the performance of male and female employees.